1993
DOI: 10.1111/j.1600-051x.1993.tb00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between mechanical cleaning and an antimicrobial rinse for the treatment and prevention of interdental gingivitis

Abstract: This study compared the efficacy of an antimicrobial mouthrinse (0.12% chlorhexidine gluconate) plus toothbrushing (mouthrinse group), mechanical interdental cleaning plus toothbrushing (mechanical group), and toothbrushing alone (control group), at reducing and preventing interdental gingival inflammation. 92 male subjects were examined for interdental inflammation using the Eastman interdental bleeding index at baseline, then monthly for 3 months after using one of the above oral hygiene regimens. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 29 publications
0
23
2
3
Order By: Relevance
“…Clinical studies 24,28,29 involving critically ill patients have shown that inadequate salivary flow promotes the development of pharyngeal mucositis and increased colonization by aerobic pathogens. The presence of endotracheal or feeding tubes contributes to the formation of biofilms strongly resistant to antiseptics or antibiotics.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies 24,28,29 involving critically ill patients have shown that inadequate salivary flow promotes the development of pharyngeal mucositis and increased colonization by aerobic pathogens. The presence of endotracheal or feeding tubes contributes to the formation of biofilms strongly resistant to antiseptics or antibiotics.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…15 Caton et al 28 found that rinsing with chlorhexidine solution before mechanical cleaning had a profound and sustained effect on the aerobic and facultative flora of the oral cavity and may contribute to a variety of clinical benefits. A meta-analysis 29 of the efficacy of topical chlorhexidine for prevention of VAP indicated that topical chlorhexidine is beneficial in preventing VAP and that the benefit is most marked in cardiac surgery patients.…”
Section: Chlorhexidinementioning
confidence: 99%
“…Self-performed mechanical plaque removal is an unquestioned method of controlling plaque and gingivitis 4,8,14 . However, toothbrushing and flossing are difficult tasks, and most of the patients are not able to completely remove plaque in all teeth surfaces 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity to interact not only with bacterial deposits, but also with morphological and histological characteristics of gingival tissues [4, 5, 25], provides a valuable opportunity for the clinician. Many clinical and biological concepts support the relevance of correctly stimulated interproximal tissues.…”
Section: Discussionmentioning
confidence: 99%